2010
DOI: 10.1111/j.1742-7924.2010.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of telephone follow‐up on adherence to a diabetes therapeutic regimen

Abstract: Aim: To determine whether a nurse telephone follow-up service could improve the level of adherence to a diabetes therapeutic regimen for patients with type 2 diabetes. Methods: A total of 61 patients attended a 3 day diabetes self-care program at the Iranian Diabetes Society. They were randomly assigned to one of the experimental or control groups. A telephone follow-up program was applied to the experimental group for 3 months, twice per week for the first month and weekly for the second and third months. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(151 citation statements)
references
References 25 publications
4
143
0
4
Order By: Relevance
“…It is necessary to point out that 'mobile phone intervention' meant intervention using the mobile phones with or without internet for diabetes self-management, and hence, we pooled data from 12 studies (14,15,16,17,18,20,21,23,24,26,27,30) that used a similar intervention. Compared with the study by Liang et al, we consider that our results had several strengths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is necessary to point out that 'mobile phone intervention' meant intervention using the mobile phones with or without internet for diabetes self-management, and hence, we pooled data from 12 studies (14,15,16,17,18,20,21,23,24,26,27,30) that used a similar intervention. Compared with the study by Liang et al, we consider that our results had several strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reported improvement in HbA1c. Four studies (19,22,23,24) scored A for quality, nine (13,14,15,17,18,20,25,26,27) Fig. 2).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…Another survey with 13 questions was applied in order to record variables such as height, weight, body mass index (BMI), systolic arterial pressure (SAP) and diastolic arterial pressure (DAP), waist circumference (WC), fasting blood glucose, low density lipoprotein (CLDL), high density lipoprotein (CHDL), triglycerides, total cholesterol level, and glycosylated hemoglobin (HbA). A pilot study was conducted from March to April in 2013, with five patients receiving medical The intervention consisted of supportive telephone calls based on national (6)(7) and international studies (12)(13)(14) . The education program was elaborated according to support for self-care (15) and the cognitive behavioral approach (16) , and also followed the guidelines of the Brazilian Diabetic Society (17) .…”
Section: Study Protocolmentioning
confidence: 99%
“…The addition of one, two, three or four phone calls during the focused intervention led to corresponding increases in HbgA1c testing adherence compared to no telephone calls. Nesari, et al (2010) [16] focused on the impact of telephone follow-up interventions on the HbgA1c in patients with type 2 diabetes. The nurse-led telephone follow up intervention was effective in enhancing the level of adherence to diabetes therapeutic regimen, evidenced by decreased HbgA1c level.…”
Section: Telephone Follow-up Callsmentioning
confidence: 99%